#TITLE_ALTERNATIVE# - MANGOPO (NIM : 15109069) ; pembimbing : Dr. Ir. Samsul Bachri, M.Eng, MIKHAEL
Multibeam Echosounder (MBES) is an instrument that using the principle of SONAR technology with the concept of acoustic waves, where as the sound speed is a key factor for applying this technology, the topic is to study how to identify the accuracy of the sound velocity profile (SVP) which is for processing the MBES data. Identification of SVP data accuracy is important because it determines the quality of the data generated from the depths of MBES data. identification of SVP data accuracy can be done in post-processing the MBES data using CARIS HIPS 6.0 software by do a visual analysis on the resulting surface. From the study, it was concluded that the SVP data used in the processing is not accurate that the object in the form of a mound at the visual analysis of the surface resulting from the post-processing of data is not a true representation of the sea floor and this causes the need to do the cutting process at the outerbeam depth to reduce the effect.